Design and Configuration of a Tridyne Propulsion System for CubeSat Applications - Sciuto III, Peter J. (My University, 2021)
A warm-gas thruster using a catalyzed tridyne propellant (88% N2, 8% H2 and 4% O2 by volume) is developed at the University of Washington in collaboration with Aerojet Rocketdyne for the purposes of advancing small-scale satellite propulsion. A detailed design of a 1.5U (10 cm x 10 cm x 15 cm) CubeSat propulsion unit has been developed in a configuration suitable for space applications. The design incorporates accumulator volumes to allow for pressure regulation as well as pulse-modulating the thrust chamber pressure in a “bang-bang” fashion, has all welded joints for space application, and has all material compatibility issues addressed. Though the primary focus of the effort is the development of a thruster configuration for integration into a CubeSat form factor, the work also includes testing of the thruster configuration, including successful demonstration of the bang-bang pressure control system.
Thesis (Master's)--University of Washington, 2021
Keywords: CubeSat; Propulsion; Satellite; Tridyne; Aerospace engineering; Fluid mechanics; Aeronautics and astronautics